INSILICO STUDIES OF OXIME PRODRUG OF GLICLAZIDE AGAINST SULPHONYLUREA RECEPTORS (SUR 1) - Vijayaraj, Surendran; Veena, Kannekanti Chaithanya (International Journal of Current Pharmaceutical Research, 2017)
Objective: Objective of the study is to perform a molecular docking analysis of novel oxime prodrug of gliclazide against SUR1 receptor. Methods: Sulfonylurea receptors (SUR) are membrane proteins which are the molecular targets of the sulfonylurea class of anti-diabetic drugs whose mechanism of action is to promote insulin release from pancreatic beta cells. Oxime prodrug of gliclazide a better soluble derivative of gliclazide is used for enhancement of bioavailability of gliclazide. Autodock 4.2 software was used for docking studies. Ligand 2D structures were drawn using ChemDraw Ultra 7.0. Binding sites, docking poses and interactions of the ligand with SUR1 receptors were studied by pymol software. Results: The docking studies suggest that potential binding sites of oxime prodrug of gliclazide exhibiting all the major interactions such as hydrogen bonding, hydrophobic interaction and electrostatic interaction with GLU43, LEU11, LEU 40, ILE17 GLU 68, GLN72 residues of SUR1. The binding energy of complexes are also found to be minimal forming stable complexes. Conclusion: In silico study of oxime prodrug of gliclazide conforms, the binding of oxime prodrug of glicalzide with SUR1 receptors which effectively controls the release insulin to regulate plasma glucose concentrations. Hence, the oxime prodrug of gliclazide could be a potent anti-diabetic target molecule which may be worth for further in vitro and in vivostudies.